2017
DOI: 10.1371/journal.pone.0189055
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic position and ten-year survival and virologic outcomes in a Ugandan HIV cohort receiving antiretroviral therapy

Abstract: Lifelong ART is essential to reducing HIV mortality and ending the epidemic, however the interplay between socioeconomic position and long-term outcomes of HIV-infected persons receiving antiretroviral therapy (ART) in sub-Saharan Africa is unknown. Furthering the understanding of factors related to long-term ART outcomes in this important region will aid the successful scale-up of ART programs. We enrolled 559 HIV-infected Ugandan adults starting ART in 2004–2005 at the Infectious Diseases Institute in Kampal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 34 publications
(31 reference statements)
3
21
1
Order By: Relevance
“…Given that most of the evidence on the recovery of NK cells is from individuals after a short duration of ART, there is need to explore recovery of NK cell function after longer durations of ART. This is particularly important for sub-Saharan Africa which has more than 10 million people receiving ART majority of whom have been on treatment for more than 10 years [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given that most of the evidence on the recovery of NK cells is from individuals after a short duration of ART, there is need to explore recovery of NK cell function after longer durations of ART. This is particularly important for sub-Saharan Africa which has more than 10 million people receiving ART majority of whom have been on treatment for more than 10 years [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…barriers to care), emotional health, social support, and competing needs at the time of diagnosis, also likely to have an important effect on survival [16,17]. In addition, most mortality studies, including those that have examined social and contextual factors, have limited analyses to HIV-infected individuals [7,[18][19][20][21][22][23]. Little is known about contextual factors that predict long-term mortality in resource-limited settings, for both HIV-infected and HIV-uninfected individuals.…”
mentioning
confidence: 99%
“…There is mixed evidence regarding the association between socioeconomic status and short-term mortality among HIV-infected individuals initiating ART [1215]. We found that greater years of education and employment were protective, and unemployment was also associated with not initiating ART (many non-initiators were known mortalities).…”
Section: Discussionmentioning
confidence: 67%
“…Prior studies in sub-Saharan Africa and other settings have identified sociodemographic predictors of early mortality including male gender [7, 911] and older age [7, 9, 10]. Measures of lower socioeconomic status [12, 13] and single marital status [13] have also been identified in some, though not all [14, 15] studies that investigated these factors. Clinical predictors of mortality include low CD4 count [7, 9, 10, 16] and low body mass index (BMI), weight loss, and malnutrition [7, 16].…”
Section: Introductionmentioning
confidence: 99%